"I Want to See People's Reactions to the Selfies": A Lefebvrian Analysis of the Impact of Social Networking Sites on Physical, Mental, and Emotional Functioning. (June 2022) - Harkin, Ben; Yates, Alan; Riach, Martin; Clowes, Alice; Cole, Sophie; Cummings, Claudia
Since the conception and exponential growth of social networking sites (SNSs), technology has advanced sufficiently to allow access to them at any moment for any reason. This has given users a "virtual space" (VS) in which to communicate and "live" within (e.g., Facebook), a space which disparate research has shown to have an impact on users' behaviors, thoughts, and emotions. The present study aimed to examine the potential for SNSs to influence the physical, mental, and social well-being of undergraduate students. To explore this in a unified fashion, we conducted in-depth interviews with 25 participants across three qualitative studies. All interview transcripts were analyzed using a recursive deductive thematic analysis. Lefebvre's trialectic of space was examined for its applicability to students' experiences of VS vis-à-vis SNSs. Lefebvre's spatial triad provides a novel and coherent framework to untangle and explain the multifaceted and often complicated nature of SNS use. Analysis found correspondence between Lefebvrian triadic space and SNSs to explain the pervasive, dominant, and sometimes pathological role that SNSs can have upon everyday functioning. Implications are that a Lefebvrian approach can inform future research as a means to untangle and explain the multifaceted and often complicated nature of SNS use.